White-rot fungi scavenge reactive oxygen species, which drives pH-dependent exo-enzymatic mechanisms and promotes CO2 efflux - Jofré-Fernández, Ignacio; Matus-Baeza, Francisco; Merino-Guzmán, Carolina (Frontiers in Microbiology, 2023)
Soil organic matter (SOM) decomposition mechanisms in rainforest ecosystems are governed by biotic and abiotic procedures which depend on available oxygen in the soil. White rot fungi (WRF) play an important role in the primary decomposition of SOM via enzymatic mechanisms (biotic mechanism), which are linked to abiotic oxidative reactions (e.g. Fenton reaction), where both processes are dependent on reactive oxygen species (ROS) and soil pH variation, which has yet been studied. In humid temperate forest soils, we hypothesize that soil pH is a determining factor that regulates the production and consumption of ROS during biotic and abiotic SOM decomposition. Three soils from different parent materials and WRF inoculum were considered for this study: granitic (Nahuelbuta, Schizophyllum commune), metamorphic (Alerce Costero, Stereum hirsutum), and volcanic-allophanic (Puyehue, Galerina patagonica). CO2 fluxes, lignin peroxidase, manganese peroxidase, and dye-decolorizing peroxidase levels were all determined. Likewise, the production of superoxide anion (O2•-), hydrogen peroxide (H2O2), and hydroxyl radicals (•OH) were assessed in soils microcosms after 36 days of anaerobic incubation with WRF inoculum and induced Fenton reaction under pH variations ranging from 2.5 to 5.1. ROS significantly increased biotic and abiotic CO2 emissions in all tested soils, according to the findings. The highest values (217.45 mg C kg-1) were found during the anaerobic incubation of sterilized and inoculated soils with WRF at a natural pH of 4.5. At pH 4.0, the lowest levels of C mineralization (82 mg C kg-1) were found in Nahuelbuta soil. Enzyme activities showed different trends as pH changed. The Fenton reaction consumed more H2O2 between pH 3 and 4, but less between pH 4.5 and 2.5. The mechanisms that oxidized SOM are extremely sensitive to variations in soil pH and the stability of oxidant radical and non-radical compounds, according to our findings.